2009
DOI: 10.15835/nsb113498
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Selection for Salt Tolerance in Alfalfa (Medicago sativa L.) Ecotypes via Physiological Traits

Abstract: Salt stress is a serious environmental problem throughout the world which may be partially relieved by breeding cultivars that can tolerate salt stress. Plant breeding may provide a relatively cost effective short-term solution to the salinity problem by producing cultivars able to remain productive at low to moderate levels of salinity. Five alfalfa cultivars, 'Seyah-Roud' , ' Ahar-Hourand' , 'Oskou' , 'Malekan' and 'Sefida-Khan' were assessed for salt tolerance at mature plant stage. A greenhouse screening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Salt tolerance plant species show an increase in Chl content, when grown under saline conditions (Khan et al, 2009 ; Akram N. A. and Ashraf, 2011 ), This lead to the concept that salt tolerant plant species with high Chl content exhibit greater membrane stability and higher Chl pigment content. So far, several salt tolerant plant species such as pea ( Pisum sativum ) (Noreen et al, 2010 ), melon ( Cucumis melo ) (Romero et al, 1997 ), sunflower (Akram N. A. and Ashraf, 2011 ), wheat (Raza et al, 2006 ; Arfan et al, 2007 ), alfalfa (Monirifar and Barghi, 2009 ), and proso millet ( Panicum miliaceum ) (Sabir et al, 2009 ) have been screened for their salt tolerance capacity. In contradiction to the aforementioned salt screening strategy, Juan et al ( 2005 ) observed weak linkage between leaf Na + level and photosynthetic pigment content in tomato ( Solanum lycopersicum ) plants, indicating that chlorophyll content assimilation is not always associated with salt tolerance, but is an indicator of saline conditions, depending on the plant species (Juan et al, 2005 ).…”
Section: Major Factors Limiting Photosynthesis and Plant Growthmentioning
confidence: 99%
“…Salt tolerance plant species show an increase in Chl content, when grown under saline conditions (Khan et al, 2009 ; Akram N. A. and Ashraf, 2011 ), This lead to the concept that salt tolerant plant species with high Chl content exhibit greater membrane stability and higher Chl pigment content. So far, several salt tolerant plant species such as pea ( Pisum sativum ) (Noreen et al, 2010 ), melon ( Cucumis melo ) (Romero et al, 1997 ), sunflower (Akram N. A. and Ashraf, 2011 ), wheat (Raza et al, 2006 ; Arfan et al, 2007 ), alfalfa (Monirifar and Barghi, 2009 ), and proso millet ( Panicum miliaceum ) (Sabir et al, 2009 ) have been screened for their salt tolerance capacity. In contradiction to the aforementioned salt screening strategy, Juan et al ( 2005 ) observed weak linkage between leaf Na + level and photosynthetic pigment content in tomato ( Solanum lycopersicum ) plants, indicating that chlorophyll content assimilation is not always associated with salt tolerance, but is an indicator of saline conditions, depending on the plant species (Juan et al, 2005 ).…”
Section: Major Factors Limiting Photosynthesis and Plant Growthmentioning
confidence: 99%
“…cv El Golea was insignificant, with similar results reported by Yang and others (2013). Several authors have associated proline accumulation with salt tolerance (Delauney and Verma 1993;Monirifar and Barghi 2009) whereas others reported the absence of a correlation (Perez-Alfocea and others 1993; Boughalleb and others 2011). The significance of proline accumulation in osmotic adjustment is still debated and varies according to the species.The data in Table 5 showed that although the content of soluble sugars remained stable in all treatments, all changes observed after inoculation and/or the imposition of salt stress were not significant.…”
Section: Osmolyte Accumulationmentioning
confidence: 99%
“…Genetic variability of salt tolerance exists within populations and it has been used for selection of salt-tolerant alfalfa (Kapulnik et al, 1989 ; Johnson et al, 1992 ). Physiological traits related to salt tolerance have also been investigated and used as factors for improving alfalfa salt tolerance (Ashraf et al, 1986 ; Monirifar and Barghi, 2009 ). Although efforts have been made on the selection of salt-tolerant alfalfa using traditional breeding (Smith et al, 1994 ; Scasta et al, 2012 ) and genetic engineering (Liu et al, 2011 ; Zhang and Wang, 2015 ), few salt-tolerant cultivars have been released.…”
Section: Introductionmentioning
confidence: 99%